Brain is also a Dependent Variable: Biocultural Coconstruction of Developmental Plasticity Across the Life Span. - Li, Shu-Chen (Research in Human Development, 2008)
This article reviews the emerging trend of interdisciplinary research aiming at exploring the effects of sociocultural influences on human brain functioning. Recent coconstructive views of brain development and functioning and empirical evidence of developmental plasticity at different levels are reviewed. Empirical findings that are indicative of reciprocal influences of environmental inputs, expertise, and cognitive training are highlighted. Links between age differences in neuromodulation and associative memory plasticity are illustrated as an example of cross-level interactions from molecular mechanisms to behavior. The quest to understand how individual brains get personalized through life-span development that takes place in the macro sociocultural experiential context is still at an embryonic stage. Nevertheless, studies reviewed here indicate that new conceptual and empirical opportunities for this endeavor are emerging.